(untitled) (Lex localis - Journal of Local Self-Government, 2024)
This study delves into the expansion and framework of India’s Competition Law (CL), with a primary focus on the Competition Act, 2002, and the pivotal role of the “Competition Commission of India (CCI)” in fostering fair market competition. Consumers should be guaranteed the bottom feasible prices for the utmost quality goods & services through competition legislation. By controlling market forces, CL aims to guarantee that buyers can choose from a variability of products and facilities offered at fair prices. This study intends to synthesize information from these secondary sources by means of content analysis, comparative evaluation, and legal analysis; the goal is to offer thorough a picture of India’s present CL. Relying on pre-existing data and possible biases in sources are limitations that the study recognizes. The overarching goal of the study is to shed light on the current state and potential future developments of India’s framework for CL as it pertains to protecting consumers’ rights in the marketplace.